2017
DOI: 10.25081/josac.2017.v26.i1.801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scheduling of drip irrigation on growth, yield and water use efficiency of turmeric (Curcuma longa L.) var. CO 2

Abstract: Field experiments were conducted during 2012–13 and 2013–14 at Horticulture College and Research Institute, Coimbatore (Tamil Nadu) on black clay loam soil to study the effect of scheduling of drip irrigation on the growth, yield and water use efficiency of turmeric (cv. CO 2). The experiment included two intervals and three levels of irrigation with surface irrigation as control. Significantly higher rhizome yield was recorded in one day interval of irrigation at 80% PE (T2) (42.79 t ha-1) which was on par wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In addition, studies have shown that radiation requirements in ginger and turmeric vary across the different growing stages. In general, plants benefit from shade during early field establishment but can make use of additional light and warmer temperatures for photosynthesis as they grow and produce more shoots and rhizomes [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that radiation requirements in ginger and turmeric vary across the different growing stages. In general, plants benefit from shade during early field establishment but can make use of additional light and warmer temperatures for photosynthesis as they grow and produce more shoots and rhizomes [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Drip irrigation may increase water application efficiency and decreases water losses [2]. Further, water use efficiency and plant growth (the number of leaves, leaf area, plant height, and matter production) increases significantly with drip irrigation compared to flood irrigation [3]. In another study, subsurface drip irrigation treatments had significantly increased yield; improved crop quality; reduced water application; and reduced agronomic costs for weed control, fertilization, and tillage [4].…”
Section: Introductionmentioning
confidence: 97%
“…Drip irrigation has high efficiency and reduces water losses [2]. Chitra et al [3] studied the effect of drip irrigation on water use efficiency, plant growth, and yield of turmeric compared with flood irrigation. They found significant increases in water use efficiency and plant growth (number of leaves, leaf area, plant height, and matter production).…”
Section: Introduction 1backgroundmentioning
confidence: 99%